2017
DOI: 10.1161/jaha.116.004878
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow–Derived MicroRNA‐223 Works as an Endocrine Genetic Signal in Vascular Endothelial Cells and Participates in Vascular Injury From Kawasaki Disease

Abstract: BackgroundKawasaki disease (KD) is now the most common cause of acquired cardiac disease in children due to permanent coronary artery damage with unknown etiology. The study sought to determine the role of blood microRNA miR‐223 in KD and KD‐induced injuries in vascular endothelial cells (ECs) as well as the mechanisms involved.Methods and ResultsMicroRNA profiles in serum from patients with KD and from healthy controls were assessed by microarray analysis. We noted that multiple serum microRNAs were aberrantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 27 publications
(93 reference statements)
2
55
0
Order By: Relevance
“…Recently, one research showed that, the mechanism of miRNA-involved blood vessel damage, particularly the protective mechanism, remains unclear. One research showed that KD-induced endothelial cell apoptotic could be inhibited by knockdown of miR-223, which was up-regulated in KD serum [3]. In addition, Another study showed that miR-125a-5p increased in plasma induced endothelial cell apoptotic [29].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, one research showed that, the mechanism of miRNA-involved blood vessel damage, particularly the protective mechanism, remains unclear. One research showed that KD-induced endothelial cell apoptotic could be inhibited by knockdown of miR-223, which was up-regulated in KD serum [3]. In addition, Another study showed that miR-125a-5p increased in plasma induced endothelial cell apoptotic [29].…”
Section: Discussionmentioning
confidence: 99%
“…We previously revealed that many miRNAs, including miR-27b, are differentially expressed in serum from KD patients compared with healthy children [3]. However, the functions of these miRNAs in KD are not clear.…”
Section: Mir-27b Is Increased In Kd Serum and Mir-27b Levels In Serummentioning
confidence: 99%
See 3 more Smart Citations